2011
DOI: 10.1093/jscr/2011.8.6
|View full text |Cite
|
Sign up to set email alerts
|

Adenomyoma of ampulla: a rare cause of obstructive jaundice

Abstract: Adenomyoma is a rare benign lesion occurring commonly in the fundus of the gallbladder in the biliary tract. Ampullary adenomyoma is rarer still, presenting as obstructive jaundice due to its location at the ampulla and may mimic malignancy on clinical and radiological examination. Endoscopic biopsy may not be always diagnostic if the lesion is deep seated. Histologically these lesions show a combination of diverse benign epithelial and mesenchymal elements, which should not be confused with an invasive tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…3 To date, 58 cases of adenomyoma of the major papilla have been described in the English literature. 3,6,[11][12][13][14][15][16] However, adenomyoma of the minor papilla is extremely rare, with only one case reported. 7 Although a previous review in 1999 showed a higher prevalence in women, with a female/male ratio of 3:1, 17 we did not find any significant difference after reviewing all cases published to date.…”
Section: Discussionmentioning
confidence: 99%
“…3 To date, 58 cases of adenomyoma of the major papilla have been described in the English literature. 3,6,[11][12][13][14][15][16] However, adenomyoma of the minor papilla is extremely rare, with only one case reported. 7 Although a previous review in 1999 showed a higher prevalence in women, with a female/male ratio of 3:1, 17 we did not find any significant difference after reviewing all cases published to date.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the introduction of calcineurin based immunosuppressive therapy (especially tacrolimus), the improved surgical outcomes and graft survival has resulted in an increase in the number of PTA's conducted, which as of December 2011 accounted for 7.7% of all US pancreas transplantations reported to the IPTR [3]. PTA is usually reserved for patients with a GFR of >80 mls/min/1.73 m 2 , without proteinuria (or with mild stable proteinuria) [2].…”
Section: Types Of Pancreas Transplantationmentioning
confidence: 99%
“…In the past 48 years, Pancreatic transplantation has evolved from being entirely experimental to becoming a well established therapeutic modality [3], with more than 37,000 surgeries worldwide, being reported to the international pancreas transplantation registry (IPTR) in the year 2010 [3]. Most of the pancreas graft recipients usually have type 1 diabetes; however, about 7.7% have type 2 diabetes [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, small adenomyomas (2–5 mm) are common and reported in 60% of the population in autopsies, with no relevant associated clinical history ( 2 ). Adenomyoma in the AOV is usually detected incidentally without symptoms ( 2 3 ), but it may manifest symptoms such as abdominal pain and jaundice when the lesion causes biliary obstruction ( 5 6 ).…”
Section: Introductionmentioning
confidence: 99%